Konsep Pembagian Waris dalam Kitab Fathul Wahhab pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: The Concept of Distribution of Inheritance in the Book of Fathul Wahhab in Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Lili Aisyah Damayanti; Nur Aisyah Khoiril Aqilah; Marisa Selviana; Syarifah Nur Aisah; Salma Safira Az-zahra (Litera Academica Publishing, 2025)
This study discusses the concept of inheritance distribution in Kitab Fathul Wahhab by Shaykh Zakariya al-Anshari and its application in the learning process at Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta. The research employs a descriptive qualitative method with a combination of library research and field interviews. The findings show that Fathul Wahhab explains inheritance distribution based on four main elements: pillars, causes, impediments, and heirs, with portions determined by Islamic law, namely ½, ¼, ⅛, ⅔, ⅓, and ⅙. This distribution reflects a balanced form of justice according to social responsibility and kinship proximity. In the pesantren learning context, the book is used to strengthen students’ understanding of faraidh (Islamic inheritance law) through the sorogan and bandongan methods. Overall, Fathul Wahhab plays an essential role in preserving the Islamic scholarly tradition and shaping a fair and contextual understanding of inheritance law within the pesantren environment.